2010
DOI: 10.1073/pnas.1015493108
|View full text |Cite
|
Sign up to set email alerts
|

Distortions of mind perception in psychopathology

Abstract: It has long been known that psychopathology can influence social perception, but a 2D framework of mind perception provides the opportunity for an integrative understanding of some disorders. We examined the covariation of mind perception with three subclinical syndromes-autism-spectrum disorder, schizotypy, and psychopathy-and found that each presents a unique mind-perception profile. Autism-spectrum disorder involves reduced perception of agency in adult humans. Schizotypy involves increased perception of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
133
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(161 citation statements)
references
References 23 publications
11
133
1
1
Order By: Relevance
“…Thus, they note that psychopaths show deficits with regard to emotional recognition and empathy. Further, in a replication of Gray et al's (2007) study conducted by Gray, Jenkins, Heberlein, and Wegner (2011), scores on the Self-Report Psychopath Scale were found to be associated with lower ratings for Experience for both humans and animals.…”
Section: Building Off Of the Work Of Gray And Colleagues Knobe And Pmentioning
confidence: 49%
“…Thus, they note that psychopaths show deficits with regard to emotional recognition and empathy. Further, in a replication of Gray et al's (2007) study conducted by Gray, Jenkins, Heberlein, and Wegner (2011), scores on the Self-Report Psychopath Scale were found to be associated with lower ratings for Experience for both humans and animals.…”
Section: Building Off Of the Work Of Gray And Colleagues Knobe And Pmentioning
confidence: 49%
“…[49][50][51] One behavioural study using a huge number of participants, found that ASD showed reduced perception of agency, whereas SCZ showed increasing perception of agency in human but also in other entities (animals and objects). 52 Inconsistent results come also from brain volumetric studies: A meta-analysis study reported similar brain volumes between ASD and SCZ, but also clear distinctions. 53 In 2 different EEG-studies using the same paradigm, ASD and SCZ were separately tested regarding their social-emotional abilities 54,55 revealing overlapping but opposite results (reduced Mu suppression in ASD and larger Mu suppression in SCZ).…”
Section: Discussionmentioning
confidence: 99%
“…Aussi, contrairement à ce que certains roboticiens suggéraient, cette réticence à l'égard des robots « trop » humains semble exister, y compris pour les jeunes, c'est-à-dire pour les futurs usagers potentiels de ces robots. En effet, la conception de robots anthropomorphes ne s'accompagne pas forcément d'attitudes positives à leur égard (Gray & Wegner, 2012 ;Gray, Gray, & Wegner, 2007 ;Gray, Jenkins, Heberlein, & Wegner, 2011).…”
Section: Conclusion Et Discussionunclassified